Dry season and soil texture affect the chemical control of monocotyledonous in sugarcane - Takano, Hudson Kagueyama; Biffe, Denis Fernando; Constantin, Jamil; Oliveira Junior, Rubem Silvério de; Braz, Guilherme Braga Pereira; Gemelli, Alexandre (Comunicata Scientiae, 2018)
The chemical weed control in sugarcane during the wet season is more effective than the control carried out during the dry season. The objective of this study was to evaluate the efficacy of herbicides in the rainy season and in the dry season in sugarcane crop, and in different soil textural classes. The experiments simulated dry season and rainy season basing on periods of days in which experiment was submitted to irrigation restriction. In each experiment, it was tested 50 and 100% of the dose of the main herbicides commonly used in sugarcane to control B. decumbens, B. plantaginea, P. maximum and D. horizontalis. In general, in dry conditions, as well as varying the soil texture, there are restrictions in the choice of herbicide to be used due to the reduced effectiveness of some treatments in certain situations. In the very-clayey soil, especially in the dry season, the efficacy of herbicides is better, whereas, for the sandy-clay-loam soil in dry conditions, the effectiveness of herbicides is restricted. Thus, this study, despite the great complexity of the variables to be analyzed, permitted to establish guidelines for decision making on the most appropriate herbicide to be applied in each studied condition, in order to control these weed species.